Flexible spectral precoding for sidelobe suppression in OFDM systems - Khawar Hussain; Ana Lojo; R. López-Valcarce (IEEE Int. Conf. Acoustics, Speech and Signal Processing (ICASSP), 2019)
Spectral precoding is a popular approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. Since precoding will introduce signal distortion, appropriate decoding is required at the receiver side. We present a novel linear precoder design with flexibility to trade off OBR reduction, precoding/decoding complexity, and error rate at the receiver. The precoding matrices have low rank, which translates into significant computational savings. In this way, the requirements of different systems can be satisfied with varying complexity levels.
Keywords: spectrum shaping; winter